The Relationship between Gratitude and Self-Acceptance with the Quality of Life of Hypertension Patients - Ainiyah, Nur; Firdaus, Firdaus; Hasina, Siti Nur; Yuliana, Eva (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2025)
Hypertension, as one of the chronic diseases with a high prevalence, often hurts the quality of life of patients, both in physical, psychological, and social aspects. This study aims to investigate the relationship between gratitude, self-acceptance, and the quality of life of patients with hypertension in the Health Center X in Surabaya. The design of this study employs a quantitative approach with a cross-sectional design, using a population of 76 hypertension patients in the Health Center X in Surabaya. The sampling technique used is convenience sampling, involving 69 respondents. Data collection was carried out using the Gratitude Questionnaire-Six Item Form (GQ-6) scale questionnaire for gratitude, Unconditional Self-Acceptance Questionnaire (USAQ) for self-acceptance, and WHOQOL-BREF for quality of life, tested using Spearman's rank test. The results of the study showed that of the 69 respondents had gratitude (49.3%), self-acceptance (44.9%), and quality of life (69.6%). Statistical analysis using the Spearman rank test showed that there was a significant relationship between gratitude and quality of life of 0.01 (p<0.05) while self-acceptance and quality of life with a correlation value of 0.03 (p<0.05). Therefore, it is hoped that respondents with hypertension will always be grateful and confident in the blessings, successes, or opportunities in life so that good things happen, both big and small, and appreciate them with a sense of trust and. To improve the quality of life, hypertension sufferers should adopt a healthy low-salt diet by increasing the consumption of fruits and vegetables, routinely doing physical activities such as walking or cycling for at least 30 minutes every day, as well as maintaining ideal body weight and managing stress well so that blood pressure remains controlled and the risk of complications can be minimized. ABSTRAK Hipertensi sebagai salah satu penyakit kronik dengan prevalensi tinggi seringkali mengganggu kualitas hidup penderitanya, baik secara fisik, psikologis, maupun sosial. Penelitian ini bertujuan untuk mengetahui hubungan rasa syukur, penerimaan diri, dengan kualitas hidup penderita hipertensi di Puskesmas X Surabaya. Desain penelitian ini menggunakan pendekatan kuantitatif dengan rancangan cross sectional, dengan menggunakan populasi sebanyak 76 penderita hipertensi di Puskesmas X Surabaya. Teknik pengambilan sampel yang digunakan adalah convenience sampling dengan jumlah responden sebanyak 69 orang. Pengumpulan data dilakukan dengan menggunakan kuesioner skala Gratitude Questionnaire-Six Item Form (GQ-6) untuk rasa syukur, Unconditional Self-Acceptance Questionnaire (USAQ) untuk penerimaan diri, dan WHOQOL-BREF untuk kualitas hidup yang diuji menggunakan uji rank Spearman. Hasil penelitian menunjukkan dari 69 responden memiliki rasa syukur (49,3%), penerimaan diri (44,9%), dan kualitas hidup (69,6%). Analisis statistik menggunakan uji Spearman Rank menunjukkan bahwa terdapat hubungan yang signifikan antara rasa syukur dengan kualitas hidup sebesar 0,01 (p<0,05) sedangkan penerimaan diri dengan kualitas hidup dengan nilai korelasi sebesar 0,03 (p<0,05). Oleh karena itu, diharapkan kepada responden penderita hipertensi agar selalu bersyukur dan yakin terhadap nikmat, keberhasilan, atau kesempatan dalam hidup sehingga terjadi hal-hal baik, baik yang besar maupun yang kecil, serta mensyukurinya dengan rasa percaya dan. Untuk meningkatkan kualitas hidup, sebaiknya penderita hipertensi menerapkan pola makan sehat rendah garam dengan memperbanyak konsumsi buah dan sayur, rutin melakukan aktivitas fisik seperti jalan kaki atau bersepeda minimal 30 menit setiap hari, serta menjaga berat badan ideal dan mengelola stres dengan baik agar tekanan darah tetap terkontrol dan risiko komplikasi dapat diminimalkan.